Alterações comportamentais induzidas pela ausência do ritmo circadiano de luz: Efeitos da luz constante ou escuro constante em comportamentos relacionados à depressão e na atividade locomotora em ratos - Marin, Marcelo Tadeu [UNESP]; Araújo, Túlio Teixeira; Rezende, Marina Monteiro Figueiredo; Ribeiro-Barbosa, Érika Renata (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2015)
Affective disorders have been linked to abnormal biological rhythms. Depression- and anxietyrelated behaviors can be altered following changes of daily periods of environmental light. The aim of this study was to investigate the effect of daily light cycle on both anxiety- and depressive-like behaviors of rats. Wistar male rats were exposed to constant dark or constant light during one week and compared to control animals exposed to 12/12h light/dark cycle regarding to anxiety-like behaviors and general activity on open field test and depressive-like behaviors on the forced swimming test. Data showed that rats exposed to one week of constant light exhibited increased number of quadrants crossed in the open field. No change on anxiety-like behaviors (time and quadrants crossed in the center of apparatus) was observed in the open field test. One week of constant dark increased the time of immobility behavior in the forced swimming test relative to control 12/12h light/dark treatment. Therefore, one week of continuous light induced locomotor hyperactivity and one week of continuous dark induced depressive-like behaviors following reestablishment of normal 12/12h light/dark cycle. Such data demonstrate the importance of light/dark environmental rhythm on mood changes and the significance of light/dark cycle control on behavioral studies.
Behavioral alterations induced by absence of circadian light rhythm: Effects of constant light or constant dark on depression-like behaviors and locomotor activity in rats
Keywords: Anxiety; Circadian rhythm; Depression; Locomotor activity